Agribusiness-Based Tobacco Business Development Strategy - Endang Faradilla; Andi Nuddin; Nurhaeda Nurhaeda (Agribusiness Journal, 2024)
This research was carried out in Lilirilau District, Soppeng Regency from December 2023 to February 2024. This research aims to identify the obstacles faced by tobacco farmers, and strategic programs that can be implemented for the development of Agribusiness-based tobacco farming, using the method of Interpretive Structural Modeling (ISM). Research using the ISM method does not require a large sample, so a sample of 7 people was used. This research uses primary and secondary data collection techniques and uses data collection techniques in the form of observation, interviews, questionnaires, and documentation. Data processing in research begins with editing, coding answers and processing by using Interpretive Structural Modeling (ISM). Shows that the obstacles faced by farmers in carrying out tobacco farming are price fluctuations and the shelf life of tobacco. Furthermore, there are strategic programs that need to be implemented in developing Agribusiness-based tobacco farming.